A CONSTRUCTIVIST ANALYSIS OF CHINA’S GEOPOLITICAL ECONOMIC STRATEGY TOWARD AFRICA: A CASE OF SINO-TANZANIAN SOUTH-SOUTH COOPERATION - Bimantara, Azza (Global: Jurnal Politik Internasional, 2023)
This article discusses China’s foreign policy toward African countries by examining Sino-Tanzanian South-South Cooperation (SSC). By utilising a modified, state-centric social constructivism, this study identifies domestic and international realms of China’s normative structure responsible for shaping China’s identities within the international community. It also explains how China can reconcile its competing identities between a Global South and rising great power statuses, which gives China the ability to combine its normative interest (i.e., Global South solidarity) and material interest (i.e., the geopolitical-geoeconomic strategy) into a diverse project of SSC with positive and proactive perception from Tanzania. This study contributes toward the theorisation of China’s SSC, China’s geopolitics-geoeconomy, and China’s foreign policy toward Africa at once. This study has shown that social constructivism can explain a reconciliation between a state’s normative obligation and material desire within the international community.